Clinical study of mesh repair in ventral hernia with comorbidities (diabetes mellitus and/or obesity and/or hypothyroidism) in a tertiary care hospital - Madhu BS,; Madhura ,; Divya, Divya; Shilpa V, (Asian Journal of Medical Sciences, 2024)
Background: Ventral hernias comprise the second-most common hernia presentation, or 21–35% of all hernia types in the surgical world. Ventral hernias include incisional, umbilical, epigastric, and spigelian hernias, among others. This study was undertaken to know the different clinical types, age incidence, and predisposing factors for ventral hernia and to study the complications. Aims and Objectives: This study was undertaken to know the different clinical types, age incidence, and predisposing factors for ventral hernia and to study the complications. Materials and Methods: Forty-five cases of ventral hernias treated were studied prospectively from January 2021 to June 2022, in which each patient was evaluated thoroughly and surgery was planned to obtain a satisfactory outcome. The distribution of ventral hernias with respect to age, sex, comorbidities, and risk was recorded. Common presenting symptoms of ventral hernias, diagnosis, and complications were studied. The data collected was entered in a proforma, tabulated, and statistically analyzed. Results: Females were affected much more than males. Out of the three types of hernia that were studied, umbilical hernia showed more incidence (n=23/51%), followed by incisional hernia (n=15/33%), and epigastric hernia (n=7/16%). The most common age presentation was in the fourth and fifth decades. The most common type of mesh repair was pre-peritoneal repair in 28 (62%). The pain was relatively more common post-surgery complications, as noted in 11 (24%). In 100% of the cases, swelling was the complaint, followed by pain (18.8%). Obesity was the most common etiological factor in the development of ventral hernias (60%), followed by diabetes (35%). Conclusion: The most common ventral hernia was an umbilical hernia. Ventral hernias are more common in females. Obesity and diabetes are observed to be the major predisposing risk factors. Good pre-operative evaluation and preparation, sound anatomical knowledge, and meticulous attention to surgical detail are the most important factors for the prevention of postoperative complications. In view of the limited period of follow-up, we were not in a position to comment on recurrence rates, but when proper surgical procedures are adopted along with pre-operative correction of comorbid factors, results will always be excellent.